A warm antibody mediated acute hemolytic anemia with reticulocytopenia in a four-month-old girl requiring immunosuppressive therapy - Olcay, Lale; Düzova, Ali; Gümrük, Fatma (The Turkish Journal of Pediatrics, 1999)
We present a four-month-old girl with severe hemolytic anemia and reticulocytopenia. This case is the youngest with hemolytic anemia encountered in our hospital. Findings of autoimmune hemolytic anemia were preceded by diphtheria-pertussis-tetanus (DPT) and oral polio vaccines which were given one month before. At admission, she had heart failure, her hemoglobin (Hb) was 27 gm/L, hematocrit (Hct) 8.5 percent, reticulocyte count 0.2 percent, and gamma and non-gamma Coombs tests were positive. Plasma Hb was 23 percent (N < 3%) and haptoglobin 0 mg/dl. Bone marrow aspiration smear revealed erythroid hyperplasia. No infection, immunodeficiency or malignancy could be established. She received multiple transfusions and did not respond to methyl prednisolone therapy of seven days’ duration, but was successfully treated with a combination of immunosuppressive therapy (cyclophosphamide, 6-mercaptopurine, intravenous immunoglobulin and prednisolone, which was added later). This case is interesting in that the disease was preceded by DPT vaccination, was associated with reticulocytopenia and was resistant to steroids.